I am a thief! - Rayner, Abigail (NorthSouth Books, 2019)
When Eliza Jane Murphy--line leader, captain of the worm rescue team--impulsively pockets a sparkly green stone from her classroom's "Exploring Green" display table, her heart crumples. My heart stopped singing. My letters went wonky. I was too heavy to swing! I wanted to put it back ... But what if someone saw? But when she discovers that nearly everyone in her family took something once in their lives--from her baby brother and mom, to her nana with her sausage-stealing dog--Eliza overcomes her shame to make things right. A hilarious and heartfelt story about stealing and finding the courage to do the right thing.--